Assessment of genetic markers for multilocus sequence typing (MLST) of Fasciola isolates from Iran. Issue 2 (7th November 2022) - Nazari, Naser; Rokni, Mohamad Bagher; Ichikawa‐Seki, Madoka; Raeghi, Saber; Hajjaran, Homa; Falahi, Shahab; Hamzavi, Yazdan; Heydarian, Peyman; Davari, Afshin; Ghadiri, Keyphobad; Bozorgomid, Arezoo
Abstract: Background: Several markers have been described to characterise the population structure and genetic diversity of Fasciola species ( Fasciola hepatica (F. hepatica) and Fasciola gigantica ( F. gigantica ). However, sequence analysis of a single genomic locus cannot provide sufficient resolution for the genetic diversity of the Fasciola parasite whose genomes are ∼1.3 GB in size. Objectives: To gain a better understanding of the gene diversity of Fasciola isolates from western Iran and to identify the most informative markers as candidates for epidemiological studies, five housekeeping genes were evaluated using a multilocus sequence typing (MLST) approach. Methods: MLST analysis was developed based on five genes ( ND1, Pepck, Pold, Cyt b and HSP70 ) after genomic DNA extraction, amplification and sequencing. Nucleotide diversity and phylogeny analysis were conducted on both concatenated MLST loci and each individual locus. A median joining haplotype network was created to examine the haplotypes relationship among Fasciola isolates. Results: Thirty‐three Fasciola isolates (19 F. hepatica and 14 F. gigantica ) were included in the study. A total of 2971 bp was analysed for each isolate and 31 sequence types (STs) were identified among the 33 isolates (19 for F. hepatica and 14 for F. gigantica isolates). The STs produced 44 and 42 polymorphic sites and 17 and 14 haplotypes for F. hepatica and F. gigantica, respectively. Haplotype diversity was 0.982 ± 0.026 and 1.000 ± 0.027 and nucleotide diversity was 0.00200 and 0.00353 ± 0.00088 for F. hepatica and F. gigantica, respectively. There was a high degree of genetic diversity with a Simpson's index of diversity of 0.98 and 1 for F. hepatica and F. gigantica, respectively. While HSP70 and Pold haplotypes from Fasciola species were separated by one to three mutational steps, the haplotype networks of ND1 and Cyt b were more complex and numerous mutational steps were found, likely due to recombination. Conclusions: Although HSP70 and Pold genes from F. gigantica were invariant over the entire region of sequence coverage, MLST was useful for investigating the phylogenetic relationship of Fasciola species. The present study also provided insight into markers more suitable for phylogenetic studies and the genetic structure of Fasciola parasites. Abstract : MLST analysis was developed based on five genes ( ND1, Pepck, Pold, Cyt b and HSP70 ) after genomic DNA extraction, amplification and sequencing. Thirty‐three Fasciola isolates (19 F. hepatica and 14 F. gigantica ) were obtained from the infected livers (sheep n = 16, cattle n = 48 and goat n = 4) in Kermanshah Province, Iran. Although, HSP70 and Pold genes from F. gigantica were invariant over the entire region of sequence coverage, MLST was useful for investigating the phylogenetic relationship of Fasciola species.